PENGARUH KOMPETENSI, PENGEMBANGAN PROFESIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI SMP BUKIT SION JAKARTA - Supriyati, Caecilia; Pradiani, Theresia; Fathorrahman, Fathorrahman (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Teachers have a key role in determining the quality of education at Bukit Sion Middle School, Jakarta. This research aims to examine the extent to which competence, professional development, and work environment influence teacher performance. With a quantitative approach, data was collected through questionnaires from 35 teachers and analyzed using multiple linear regression. The results show that all these factors have a significant influence on teacher performance, with professional development as the main factor, followed by competency and work environment. This research underlines the importance of a comprehensive approach to supporting teachers, through relevant training, ongoing development programs and a conducive working environment. Based on the problem formulation, research objectives, research hypothesis, data analysis, and discussion of research results, it can be concluded as follows: (1) Competency has a positive and significant effect on the performance of teachers at Bukit Sion Middle School, Jakarta; (2) Professional Development has a positive and significant effect on the performance of teachers at Bukit Sion Middle School, Jakarta; (3) The work environment has a positive and significant effect on the performance of teachers at Bukit Sion Middle School, Jakarta; (4) Competence, Professional Development, Work Environment simultaneously influence the performance of teachers at Bukit Sion Jakarta Middle. Keyword: Teacher Performance, Competency, Work Environment, Professional Development. Abstrak: Guru memiliki peran kunci dalam menentukan kualitas pendidikan di SMP Bukit Sion Jakarta. Penelitian ini bertujuan untuk mengkaji sejauh mana kompetensi, pengembangan profesional, dan lingkungan kerja memengaruhi kinerja guru. Dengan pendekatan kuantitatif, data dikumpulkan melalui kuesioner dari 35 guru dan dianalisis menggunakan regresi linier berganda. Hasilnya menunjukkan bahwa semua faktor tersebut memberikan pengaruh signifikan terhadap kinerja guru, dengan pengembangan profesional sebagai faktor utama, diikuti oleh kompetensi dan lingkungan kerja. Penelitian ini menggarisbawahi pentingnya pendekatan menyeluruh untuk mendukung guru, melalui pelatihan yang relevan, program pengembangan yang berkelanjutan, dan lingkungan kerja yang kondusif. Berdasarkan rumusan masalah, tujuan penelitian, hipotesis penelitian, analisis data, dan pembahasan hasil penelitian, maka disimpulkan sebagai berikut: (1)Kompetensi berpengaruh positif dan signifikan terhadap kinerja guru SMP Bukit Sion; (2)Pengembangan Profesioanal berpengaruh positif dan signifikan terhadap kinerja guru SMP Bukit Sion Jakarta; (3)Lingkungan kerja berpengaruh positif dan signifikan terhadap kinerja guru SMP Bukit Sion; (4)Kompetensi, Pengembangan Profesional, Lingkungan Kerja secara simultan berpengaruh terhadap kinerja guru SMP Bukit Sion. Kata kunci: Kinerja Guru, Kompetensi, Lingkungan Kerja, Pengembangan Profesional